Identification and Distribution of Marine Debris along the West Aceh Coastline - Neneng Marlian; Nurul Najmi; Eka Lisdayanti; Faliqul Isbah; Teuku Rizqi Fadillah (Institut Pertanian Bogor, 2026)
This study was undertaken in September 2023 in the West Aceh Coastal area with the goal of identifying and analyzing the distribution of marine creatures discovered at the two research sites. The sampling of marine debris was determined using a transect length of approximately 100 m. Transect distances were separated into four categories: 0, 25, 50, 75, and 100 m. Marine debris was detected using Lippiat et al. (2013) categories and NOAA (2013) size classifications. The data on the identification and distribution of marine debris was analyzed descriptively. The results revealed that organic waste (wood and its derivatives) was in the highest quantity and composition at both research stations, with 1386 (73%) and 8953 fractions (97.1%). This is followed by the number and composition of inorganic waste (plastic) at the two research stations, which are 492 fragments (26%), and 205 fragments (2.2%). The lowest amount and composition of inorganic waste (non-plastic) were found at both research stations, such as metal/metal, glass, rubber, and clothing/other fibers, namely (metal: 6 and 11; glass: 2 and 1; rubber: 2 and 28; clothing and other fibers: 18 and 24) with respective compositions ranging (metal: 0.3% and 0.1%; glass: 0.1% and 0.0%; rubber: 0.1% and 0.3%; clothing and other fibers: 0.9% and 0.3%). A one-way examination of the spatial distribution of marine debris at each research substation (Substations 1, 2, and 3) revealed no significant differences (p value > 0.05) between the two research stations. Keywords: coastal, debris, marine, West Aceh